Multiplexed color‐coded probe‐based gene expression assessment for clinical molecular diagnostics in formalin‐fixed paraffin‐embedded human renal allograft tissue. Issue 3 (3rd February 2016) - Adam, Benjamin; Afzali, Bahman; Dominy, Katherine M.; Chapman, Erin; Gill, Reeda; Hidalgo, Luis G.; Roufosse, Candice; Sis, Banu; Mengel, Michael
Abstract: Histopathologic diagnoses in transplantation can be improved with molecular testing. Preferably, molecular diagnostics should fit into standard‐of‐care workflows for transplant biopsies, that is, formalin‐fixed paraffin‐embedded (FFPE) processing. The NanoString ® gene expression platform has recently been shown to work with FFPE samples. We aimed to evaluate its methodological robustness and feasibility for gene expression studies in human FFPE renal allograft samples. A literature‐derived antibody‐mediated rejection (ABMR) 34‐gene set, comprised of endothelial, NK cell, and inflammation transcripts, was analyzed in different retrospective biopsy cohorts and showed potential to molecularly discriminate ABMR cases, including FFPE samples. NanoString ® results were reproducible across a range of RNA input quantities ( r = 0.998), with different operators ( r = 0.998), and between different reagent lots ( r = 0.983). There was moderate correlation between NanoString ® with FFPE tissue and quantitative reverse transcription polymerase chain reaction (qRT‐PCR) with corresponding dedicated fresh‐stabilized tissue ( r = 0.487). Better overall correlation with histology was observed with NanoString ® ( r = 0.354) than with qRT‐PCR ( r = 0.146). Our results demonstrate the feasibility of multiplexed gene expression quantification from FFPE renal allograft tissue. This represents a method for prospective and retrospective validation of molecular diagnostics and its adoption in clinical transplantation pathology.